2020
DOI: 10.1097/bpo.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Telemedicine Virtual Visits in Pediatric Spinal Deformity Patients: A Comparison of Feasibility and Patient Satisfaction at a Large Academic Center

Abstract: Background: Telemedicine platforms have been developed to support the convenient delivery of health care services to their patients while maintaining appropriate quality of care. However, it is unclear whether they can be utilized effectively in patients with pediatric spinal deformity (PSD). Therefore, this study aimed to evaluate the feasibility and patient satisfaction associated with virtual visit (VV) utilization in PSD patients in comparison to general pediatric orthopaedic indications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
4
46
0
Order By: Relevance
“…The potential for telemedicine to improve access to care and reduce costs lead some practices to investigate telemedicine for orthopedic outpatient care, consultation, and rehabilitation even before the COVID-19 pandemic. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] These studies demonstrated that telemedicine visits are safe, feasible, associated with high patient satisfaction, and cost-effective in patients with orthopedic concerns. 11,[15][16][17][18][19][20][21][22][23][24] Previous studies included general orthopedic, pediatric orthopedic, sports medicine, arthroplasty, and trauma practices without large numbers of adult patients presenting to spine surgeons.…”
Section: Introductionmentioning
confidence: 80%
“…The potential for telemedicine to improve access to care and reduce costs lead some practices to investigate telemedicine for orthopedic outpatient care, consultation, and rehabilitation even before the COVID-19 pandemic. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] These studies demonstrated that telemedicine visits are safe, feasible, associated with high patient satisfaction, and cost-effective in patients with orthopedic concerns. 11,[15][16][17][18][19][20][21][22][23][24] Previous studies included general orthopedic, pediatric orthopedic, sports medicine, arthroplasty, and trauma practices without large numbers of adult patients presenting to spine surgeons.…”
Section: Introductionmentioning
confidence: 80%
“…However, telephone and video appointments are preferred where possible. Virtual clinics have run successfully for many years [23][24][25], but during the COVID-19 pandemic regulations have been eased to allow greater usage [26].…”
Section: Outpatient Clinics and Telemedicinementioning
confidence: 99%
“…16 Atanda et al report a similarly large difference in average wait times, 2 minutes for telehealth vs 33 minutes for in-person, as well as average visit times, 15 minutes vs 68 minutes on average. 2 Though patients report significant time saved for telehealth appointments given the nature of a virtual visit, studies have suggested that for clinicians, telehealth requires more flexibility, and potentially more preparation and overall time spent, 12,16 though to date the literature has not explored these points in detail. In addition to saving time for patients during a single visit, telehealth services may also prevent further future utilization of resources.…”
Section: Benefits Of Telehealthmentioning
confidence: 94%